ANALISIS KOMPARASI KELAYAKAN USAHATANI PADI SEMI ORGANIK DAN NON ORGANIK PADA GAPOKTAN SALUYU DI DESA CILAMAYA, CILAMAYA WETAN, KARAWANG - Gebby Mega Agnesti; Sulistyo Sidik Purnomo; I Putu Eka Wijaya (Universitas Galuh, 2023)
The area of organic rice land has increased, but changing organic farming is not easy. Changes are made by transitioning from non-organic to semi organic farming. This prospect is very profitable but the feasibility level is not yet known. This study aims to: analyze the income of semi organic and non-organic rice farming in Gapoktan Saluyu; analyzing the feasibility of semi organic and non-organic rice farming in Gapoktan Saluyu; analyze the comparison of income and feasibility of semi organic and non-organic rice farming in Gapoktan Saluyu. The research method used is a quantitative method with. Collecting data with primary data through interviews with questionnaires, while secondary data obtained from agencies relates to research. Research respondents were 25 semi organic rice farmers and 25 non-organic farmers purposively by considering the same criteria. The analysis technique used is income, feasibility analysis by looking for the R/C ratio, and Break Event Point, an independent sample t-test on income and feasibility analysis. The results of the study: Semi organic rice farming generates an income of Rp. 19.889.970 ha/season, while non organcic is Rp. 10.188.991 ha/season, R/C ratio value of semi organic rice farming is 3,19 while non organic 1,86, BEP Production of semi organic rice farming is 2.441 kg while non organic farming is 3.344 kg, BEP price of semi organic rice farming is Rp. 1.850/kg while non organic farming is Rp. 2.985/kg, an independent sample t-test on income and feasibility it concluded that semi organic rice farming hingher than non organic rice farming